Obtenção e aplicação de quitosana de camarão "saburica", Macrobrachium jelskii (Miers, 1877) como biofilme em manga (Mangífera indica L.) minimamente processada - Santos, Mônica Carvalho (2011)
Macrobrachium jelskii is a shrimp, of a small-size, abundant in the São Francisco region in Sergipe, been known as “Saburica” by the fishermen, with a great potencial to obtain chitin. Chitin is the second more abundant polysaccharide in the nature being mainly present in the crustaceans exoskeletons and the chitosan is a polymer with a high molecular weight, result of partial deacetylation of chitin, whose characteristics are: non-toxicity substance, capacity to form resistant films, biodegradability, anti-microbial and healing activity allow the application in several different areas. In virtue of the importance of these biopolymers, the present work has been proposed with the objective of obtaining chitosan from shrimp of the Macrobrachium jelskii species and its use as edible biofilm in minimally processed mangoes, using the chitosan concentrations of 0,25%, 0,5% e 1,0%. Have been evaluated soluble solids (SS), titrable acidity (AT), ascorbic acid (AA), pH, sensory analysis and microbiological analysis of the mangoes with the chitosan coating and control. The results indicated that the chitosan biofilm used in concentration 1% had been the most efficient, keeping the color and the appearance of the mangoes. There was a linear decrease of the brightness of all samples, and the control sample presented a lower value on this attribute. Similar result was verified when this parameter was evaluated with a colorimeter. On the storage time evaluated the use of biofilm on the analysed concentrations did not show antibacterial action on minimally processed mangoes.